Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae) - Tennessen, Kenneth J.; Trapero-Quintana, Adrian; Ferreira, Francisco De Assis Cruz (Zootaxa, 2017)
The nymph of Tramea binotata (Rambur, 1842) is described and illustrated based on reared specimens from Brazil and Ecuador, and also matching nymphs from Venezuela. A new character was discovered, i.e., density of minute spiniform setae scattered on the dorsum of abdominal segments 7 & 8, that separates the Neotropical species into two groups: high density of the tiny setae separates T. binotata, T. insularis Hagen, 1861 and T. calverti Muttkowski, 1910 from the other known species which have zero to only a few of these setae. Tramea binotata is distinct from most other Neotropical species known in the nymph stage by having only 7 or 8 palpal setae, rarely 6 or 9, on one side (versus 10–12); T. calverti and T. insularis have similar low numbers of palpal setae (8–10) but each has more premental setae per side (11–14 in calverti and insularis vs. 8–10, rarely 11, in binotata). The nymphs of Tramea minuta De Marmels & Rácenis, 1982 and T. rustica De Marmels & Rácenis, 1982 are still unknown.